Development and Performance Analysis of An Automated Attendance System Based on Faced Detection - Norazman, Mohamad Amir Bin (Journal of Computing Technologies and Creative Content, 2019)
An Automated Attendance System based on face detection are focused on developing an attendance system by using a face detection. The face detection program develops using Python include with an open source algorithm for face detection, OpenCV. The program sends the data to the database as the face detected and the system will mark the attendance for the person in database as attend. The attendance can be verified through HTML output interface. The performance analysis is based on the time taken to detect number of faces and the accuracy of the face detection.